2008
DOI: 10.1016/j.drugalcdep.2007.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Familial transmission of derived phenotypes for molecular genetic studies of substance use disorders

Abstract: Although family, twin, and adoption studies indicate that genes play a significant etiologic role in the development of substance use disorders (SUDs), detecting specific genes has been difficult due to uncertainties about how to define SUDs, genetic heterogeneity and variable phenotypic expression of SUD genotypes. We used data from families recruited into six contemporaneous studies of children and adults to derive candidate SUD phenotypes using principle factors factor analysis with varimax rotation. We pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
4
1
Order By: Relevance
“…Prior family studies of ADHD have shown that ADHD and PSUD co-aggregate in families (40)(41)(42). In contrast to these findings, we did not find an increased prevalence of PSUD and nicotine dependence among the unaffected siblings of our ADHD probands.…”
Section: Discussioncontrasting
confidence: 99%
“…Prior family studies of ADHD have shown that ADHD and PSUD co-aggregate in families (40)(41)(42). In contrast to these findings, we did not find an increased prevalence of PSUD and nicotine dependence among the unaffected siblings of our ADHD probands.…”
Section: Discussioncontrasting
confidence: 99%
“…History of familial SUD has also been shown to be predictive of SUD development in ADHD . The robust co‐occurrence of ADHD and SUD in families is evidenced by the higher SUD rates among parents of children with ADHD and greater likelihood that individuals with SUD have children with ADHD or who score higher on ADHD impulsivity symptoms .…”
Section: Definition Of High‐risk Adhdmentioning
confidence: 99%
“…Debate persists as to whether greater SUD risk results from an inherent latent trait in ADHD or from the use of psychostimulants to treat the disorder . However, findings demonstrating the heritability of increased SUD risk in families with ADHD suggest that biomarkers of SUD risk in ADHD may exist before the onset of SUD . Accordingly, several groups have conducted neuroimaging studies on ADHD cohorts that have yet to develop SUD but who possess additional risk factors that further predispose them to developing SUD .…”
Section: Introductionmentioning
confidence: 99%
“…CDH13 was implicated by a GWAS of 343 ADHD adults and 250 controls 22 and in the IMAGE GWAS of ADHD symptom counts 24, 25. This gene lies under a linkage peak implicated in a meta-analysis of ADHD linkage studies 15 and has been implicated in substance use disorders 39, which co-occur with ADHD 40, 41.…”
Section: Discussionmentioning
confidence: 99%